Lectin affinity electrophoresis in a yolk sac tumour in the vagina with yolk sac tumour-type glycoform of alpha fetoprotein. Issue 10 (October 1997) - Yamamoto, R; Taketa, K; Ebina, Y; Cho, Y; Hareyama, H; Sakuragi, N; Makinoda, S; Kobayashi, K; Nishi, S; Fujimoto, S
Abstract : AIMS: To investigate a potential diagnostic use of alpha fetoprotein (alpha FP) isoform analysis by lectin affinity electrophoresis to distinguish between endodermal sinus tumours arising in the vagina in infants from those at other sites. METHODS: alpha FP in the serum of a patient with a vaginal endodermal sinus tumour was analysed for its isoforms by lectin affinity electrophoresis. The isoforms were compared with that of cord serum, sera of hepatoid adenocarcinoma of the uterus, and endodermal sinus tumour of the ovary. RESULTS: The isoforms of alpha FP obtained by lectin affinity electrophoresis in the serum of the patient with vaginal endodermal sinus tumour differed from the isoforms of alpha FP in the cord serum of normal neonates, and sera of patients with hepatoid adenocarcinoma of the uterus or endodermal sinus tumour of the ovary. CONCLUSIONS: Endodermal sinus tumour arising in the vagina could be distinguished from that in the ovary by the lectin affinity electrophoresis, and a potential diagnostic use of alpha FP isoform analysis by the lectin affinity electrophoresis for the detection of the endodermal sinus tumour in infants was demonstrated.